Enterpreneurial Talent and Intention Among Undergraduate Students: Case Study at English Language Education Department - Amri Tanduklangi; Muhammad Khusnun Muhsin; Carlina Amri (International Journal on Advanced Science, Education, and Religion, 2020)
Entrepreneurship plays an important role in generating new wealth in an economy. The growth of entrepreneurial activities will produce innovation, create new jobs for the society, trigger economic growth, and reduce unemployment rates. Eentrepreneurship is a topic requiring a lot of attentions from academicians and researchers, especially the unemployment problem arising among undergraduate students. Therefore, the aim of this article was to have a good understanding on entrepreneurial talent and intention of undergraduate university students. The antecedent factor would be measuring students’ risk taking, persuading, ambition, performer, leadership, and business management skill behavior. The subjects of the study were undergraduate students who are majoring in English at the language education department and have attended five days workshop on economic literacy program conducted by Global Economic Awareness Project (GEAP) in 2019 academic year. This research study used quantative method and a research designed survey was administered to gather questions with answers associated with a 5-point Likert scale ranging from strongly agree to strongly disagree. The questionnaires of the research used Fishbein and Ajzen’s Planned Behavior (TPB) theory, Shaver and Scott’s personal traits, and Bandura’s Self efficacy theory. The findings of the research reveal that ‘risk taking’ and ‘ambition’ factor had favorable results after students have attended short entrepreneurial course. Whereas, students’ still says “neutral” on ‘persuader’, ‘ambitious’, ‘performer’, ‘leadership’, and ‘business management factor’. It is safe to assume that students’ still had fair intention in developing their entrepreneurial interest because they have little to no experience on entreprenurial field in hand. Explicit real-life entrepreneurship related activities were recommended for future workshop to upgrade the student’s entrepreneurship talent and intention. Keywords: Entrepreneurship Talent and Intention, Global Economic Awareness, Economic Literacy Program